Integral Backstepping Approach for Mobile Robot Control - Bouzgou Kamel; Ibari Benaoumeur; Benchikh Laredj; Ahmed-Foitih Zoubir (Universitas Ahmad Dahlan, 2017)
This paper presents the trajectory tracking problem of a unicycle-type mobile robots. A robust output tracking controller for nonlinear systems in the presence of disturbances is proposed, the approach is based on the combination of integral action and Backstepping technique to compensate for the dynamic disturbances. For desired trajectory, the values of the linear and angular velocities of the robot are assured by the kinematic controller. The control law guarantees stability of the robot by using the lyapunov theorem. The simulation and experimental results are presented to verify the designed trajectory tracking control.